A política curricular da BNCC e o ensino médio: currículo e contexto - Souza, Gessica Mayara de Oliveira (2020)
Considering the curricular policies centrality in the current context, this research brings up the High School Curriculum Reform (Law number 13.415/2017) as the central theme. The problematic comes up from the results of a monograph (SOUZA, 2017) in which the relation between the public and the private sectors towards the development of the Base Nacional Comum Curricular (BNCC) was investigated. During our studies, we faced the procedure related to the provisional measure, which was numbered 746/2016, then the Law number 13.415/2017 and at last the BNCC which was getting some changes in terms of the High School in 2018 while Michel Temer was president of Brazil (2016-2018). Such events were fundamental for us to notice the need in detail our studies on the current changes in the curriculum of the Brazilian High School. After mapping researches on this field of knowledge, in which results reveal a lack of dissertations about the theme, we emphasize that it is necessary to go deep on it. That said, this work aims at identify which projects for student education unfold through curriculum conceptions presented along the three versions of the BNCC which guides the high school curriculum in Brazil. Based on such problematic, we decided that analyzing the curriculum policy of the BNCC towards identifying projects for the High School based on the curriculum conceptions is our general goal. Our analyses follow the conceptual matrices from studies by Arroyo (2011), Pereira (2013), Santos (2011); Kuenzer (1997; 2017); Macedo (2018); Lopes (2019); Apple (2001;2003); Oliveira (2013), among other authors whose researches are brought up close in this work. Methodologically, our research is based on Gonsalves (2003), Richardson (2017), Santos (2008) and Cellard (2008) studies; which characterize it as bibliographical and qualitative, considering we aim at achieving the objectives proposed in this Master’s thesis through a documental study. Therefore, we took Stephen Ball’s cycle of policies and his contributors (1987;1992;1994) as the beginning point of our investigation. Moreover, we analyzed the global context through the context of influence that reverberates in the current high school curriculum policies, just as the local context, and the context of textual production that were fundamental to our analysis. Curricula are taken as a category in this work. For that reason, we highlight that we do not have the intention of capturing a truth about the theme which is the bases for this research, but we try to present possibilities and directions for us to reflect on the Brazilian curricula policies, especially the ones related to the high school education through our own reflections, problematizations and analysis.